2005
DOI: 10.1083/jcb.200409070
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 channel is involved in the coupling of fluid viscosity changes to epithelial ciliary activity

Abstract: Autoregulation of the ciliary beat frequency (CBF) has been proposed as the mechanism used by epithelial ciliated cells to maintain the CBF and prevent the collapse of mucociliary transport under conditions of varying mucus viscosity. Despite the relevance of this regulatory response to the pathophysiology of airways and reproductive tract, the underlying cellular and molecular aspects remain unknown. Hamster oviductal ciliated cells express the transient receptor potential vanilloid 4 (TRPV4) channel, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
162
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(170 citation statements)
references
References 34 publications
(45 reference statements)
8
162
0
Order By: Relevance
“…Therefore, Ca 2ϩ entry pathways designed to modulate CBF should be localized close to the base of the cilia within the apical membrane of the cell. Previously, TRPV4 has been principally localized at the base of the cilia of hamster oviduct cells (21), and its activation by the synthetic agonist 4␣PDD increased the CBF in these cells (22). In the present study, we show that TRPV4-specific immunoreactivity is restricted mostly to cilia of TRPV4 ϩ/ϩ tracheal epithelial cells, similar to hamster oviduct ciliated cells (21) and rat ciliated cholangiocytes (31), whereas the TRPV4 signal is absent in the cilia of epithelial cells obtained from TRPV4 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Ca 2ϩ entry pathways designed to modulate CBF should be localized close to the base of the cilia within the apical membrane of the cell. Previously, TRPV4 has been principally localized at the base of the cilia of hamster oviduct cells (21), and its activation by the synthetic agonist 4␣PDD increased the CBF in these cells (22). In the present study, we show that TRPV4-specific immunoreactivity is restricted mostly to cilia of TRPV4 ϩ/ϩ tracheal epithelial cells, similar to hamster oviduct ciliated cells (21) and rat ciliated cholangiocytes (31), whereas the TRPV4 signal is absent in the cilia of epithelial cells obtained from TRPV4 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 can be also sensitized by coapplication of different stimuli (18)(19)(20) or participation of different cell signaling pathways (21). TRPV4 messenger and protein have been identified in both native ciliated epithelial cells of oviducts (21)(22)(23) and cell lines derived from human ciliated airway cells (24). In these epithelial cells, the TRPV4 channel plays a key role in cell volume homeostasis, by activating Ca 2ϩ -dependent K ϩ channels (25,26) and in the regulation of CBF, by providing a Ca 2ϩ entry pathway in response to changes in fluid viscosity or tonicity (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have demonstrated that other mediators, such as Platelet Activating Factor (PAF) may exert their stimulatory effect on CBF through an increase in PGE2 [40]. Changes in fluid viscosity has been linked to CBF with the teleologically explained aim of maintaining a constant level of CBF in the face of varying degrees of luminal fluid viscosity and it has been shown that the transient receptor potential vanilloid 4 (TRPV4) channel is involved in transmitting these extracellular signals to the intracellular ciliary apparatus [41].…”
Section: Angiotensin Systemmentioning
confidence: 99%
“…However, little is known about the mechanisms that regulate TRPV4 function in these different physiological settings, and it is unclear whether all known activation mechanisms are operating in every TRPV4-expressing cell. Heterologously expressed TRPV4 can be activated by a broad range of physical and chemical stimuli, including osmotic cell swelling (1,2,4,20,21), moderate heat (12,22), synthetic ligands stimuli as 4␣-phorbol 12,13-didecanoate (4␣-PDD) (13,23), mechanical force (14, 19, 24 -26), fluid viscosity (27), and endogenous ligands such as anandamide and arachidonic acid (AA)-derived epoxyeicosatrienoic acids (28 -30).…”
mentioning
confidence: 99%